أثر العدالة التنظيمية في زيادة الولاء التنظيمي ( دراسة ميدانية على العاملين الإدرايين في مشفى الشهيد باسل الأسد في مدينة طرطوس) - برهوم, أديب; علي, كنانة (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The following study addresses the impact of organizational justice in its four dimensions (distributive, procedural, interactive, evaluative) in increasing organizational loyalty, through conducting a field study on the administrative staff at the Martyr Bassel al-Assad Hospital in the city of Tartous. To achieve the objectives of the research, a questionnaire was constructed and distributed to a Purposive sample of (60) administrative workers In the Martyr Basel Assad Hospital. The researcher used descriptive method. The research has reached a number of results, the most important of which are: There is an intermediate relationship between organizational justice and organizational loyalty, there is no relationship between distributed justice and organizational loyalty, There is a positive relationship between (procedural, interactive, evaluative justice) and organizational loyalty. A number of recommendations were proposed, including: To promote the fairness of distribution by reviewing the policy of wages and salaries applied in the hospital under study, To promote the fairness of the procedures currently employed in the distribution of labor outputs to employees because of its positive impact on organizational loyalty to the organization, The Department of the hospital under study should provide the opportunity for the participation of workers in administrative decision-making, In particular those relating to their work in the Organization, Making them more acceptable and responsive to these decisions, Which is reflected in their organizational loyalty and performance of their duties . And their continuous motivation towards work and support for belonging. يتناول البحث الحالي أثر العدالة التنظيمية بأبعادها الأربعة( التوزيعية، الاجرائية، التفاعلية، التقييمية) في زيادة الولاء التنظيمي، من خلال اجراء دراسة ميدانية على العاملين الإداريين في مشفى الشهيد باسل الأسد في مدينة طرطوس ولتحقيق أهداف البحث تم بناء استبيان وتوزيعه على عينة قصدية بلغت (60) عامل إداري في مشفى الشهيد باسل الأسد. استخدمت الباحثة المنهج الوصفي المسحي. وقد توصل البحث الى مجموعة من النتائج أهمها: توجد علاقة متوسطة بين العدالة التنظيمية والولاء التنظيمي، لا توجد علاقة بين العدالة التوزيعية والولاء التنظيمي، توجد علاقة موجبة بين( العدالة الإجرائية، التفاعلية، التقييمية) والولاء التنظيمي. تمَ اقتراح مجموعة من التوصيات أهمها: العمل على تعزيز عدالة التوزيع وذلك من خلال اعادة النظر في سياسة الأجور والرواتب المطبق في المشفى محل الدراسة، العمل على تعزيز عدالة الإجراءات المتبعة حالياً في توزيع مخرجات العمل على العاملين لما لها من تأثير ايجابي على الولاء التنظيمي تجاه المنظمة، أن تعمل ادارة المشفى محل الدراسة على إتاحة الفرصة لمشاركة العاملين في صنع القرارات الإدارية، وخاصة تلك المتعلقة بعملهم في المنظمة، مما يؤدي إلى جعلهم أكثر قبولاً وتجاوباً مع هذه القرارات، الأمر الذي ينعكس على ولائهم التنظيمي وأدائهم لواجباتهم وتحفيزهم المستمر نحو العمل ودعمه بالانتماء.